Mechanistic insight into the efficient packaging of antigenomic S RNA into Rift Valley fever virus particles - Tercero, Breanna; Terasaki, Kaori; Narayanan, Krishna; Makino, Shinji (Frontiers in Cellular and Infection Microbiology, 2023)
Rift Valley fever virus (RVFV), a bunyavirus, has a single-stranded, negative-sense tri-segmented RNA genome, consisting of L, M and S RNAs. An infectious virion carries two envelope glycoproteins, Gn and Gc, along with ribonucleoprotein complexes composed of encapsidated viral RNA segments. The antigenomic S RNA, which serves as the template of the mRNA encoding a nonstructural protein, NSs, an interferon antagonist, is also efficiently packaged into RVFV particles. An interaction between Gn and viral ribonucleoprotein complexes, including the direct binding of Gn to viral RNAs, drives viral RNA packaging into RVFV particles. To understand the mechanism of efficient antigenomic S RNA packaging in RVFV, we identified the regions in viral RNAs that directly interact with Gn by performing UV-crosslinking and immunoprecipitation of RVFV-infected cell lysates with anti-Gn antibody followed by high-throughput sequencing analysis (CLIP-seq analysis). Our data suggested the presence of multiple Gn-binding sites in RVFV RNAs, including a prominent Gn-binding site within the 3’ noncoding region of the antigenomic S RNA. We found that the efficient packaging of antigenomic S RNA was abrogated in a RVFV mutant lacking a part of this prominent Gn-binding site within the 3’ noncoding region. Also, the mutant RVFV, but not the parental RVFV, triggered the early induction of interferon-beta mRNA expression after infection. These data suggest that the direct binding of Gn to the RNA element within the 3’ noncoding region of the antigenomic S RNA promoted the efficient packaging of antigenomic S RNA into virions. Furthermore, the efficient packaging of antigenomic S RNA into RVFV particles, driven by the RNA element, facilitated the synthesis of viral mRNA encoding NSs immediately after infection, resulting in the suppression of interferon-beta mRNA expression.